Intentional Friction in the User Interface of Digital Games - Isabella Barbosa Silva (2022)
While intentionally designing friction in gaming user interfaces may be a suitable strategy for challenging players' beliefs and prompting reflection, conventional user interface practices are frequently influenced by an overarching paradigm of user-friendliness and enjoyment. This dissertation investigates how designers might employ intentional friction in digital game user interfaces to create meaningful experiences and inspire reflection in its players. First, we review the literature to frame what constitutes interface elements in game design, the user-friendly and enjoyment paradigm, and other perspectives that offer context to using friction as a strategy. Afterward, we explore game instances that use user interface friction when appropriate as a strategy to express a point of view, to challenge current systems, or to foment critical reflection. The starting point for our observations is Donald Norman's seven design principles and Jakob Nielsen's usability heuristics. As a result, we identify six distinct intentional friction strategies. Next, we ran two co-creation workshop sessions with a total of seven participants with user interface or game design backgrounds to identify additional strategies and perspectives. The strategies gathered were collected in a deck-based tool. Finally, we ran an initial tool validation session with four participants with promising results, suggesting that the tool's friction strategies were able to drive expressiveness as an important component of the participant's discussion and ideation process. Although this work is not focused on collecting all friction design approaches indiscriminately, the identified strategies suggest more nuanced techniques than just framing the principles to create a friendly design in reverse.